Hamilton-Jacobi formalism for Podolsky's electromagnetic theory on the null-plane - Bertin, M. C. (2017)
We develop the Hamilton-Jacobi formalism for Podolsky's electromagnetic theory on the null-plane. The main goal is to build the complete set of Hamiltonian generators of the system as well as to study the canonical and gauge transformations of the theory.